Moderation through Restraint: Mahmud Yunus’s Contextual Interpretation of Qitāl and Interreligious Relations in Tafsīr al-Qur’ān al-Karīm - Muhammad Robith Fuadi; Muhammad Muhammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Religious moderation has gained increasing attention in Indonesia following the implementation of the National Medium-Term Development Plan (RPJM) 2020–2024, with the Ministry of Religious Affairs designated as the leading institution in promoting this agenda. This study aims to examine Mahmud Yunus’s moderate exegetical approach to Qur’anic verses concerning qitāl and non-Muslim relations. Using a qualitative library-based method, this research employs descriptive-analytical and thematic approaches to analyze Mahmud Yunus’s Tafsīr al-Qur’ān al-Karīm in comparison with other Nusantara exegetical works. Primary sources consist of Yunus’s tafsir, while secondary sources include relevant scholarly literature. The findings indicate that Mahmud Yunus’s work represents a moderate taḥlīlī model of Qur’anic interpretation. His exegetical approach is grounded in two key concepts: al-Ṣumt, which emphasizes restrained silence toward potentially contentious verses, and al-Taʻaṭul, which refers to the suspension of legal application in certain contexts. These concepts enable a contextual understanding of qitāl verses that avoids literalist and extremist interpretations. Consequently, Yunus’s tafsir contributes to the promotion of religious moderation by fostering interreligious tolerance while preserving the essential meaning of Qur’anic injunctions.